Modeling of lagoons and aquifers with datamine - Romero Baylón, Alfonso (2004)
The purpose of this work is to show that it is possible to model the different resources that the earth offers us (georeourses) by means of the computer tools that engineering currently has at its disposal, with the purpose of contributing to the primary extractive industry in a sustainable way. Datamine is an earth science-oriented engineering software that until now has been used in the mining sector in the modeling of metallic and non-metallic type mineral deposits. This article shows that the same tools used for the modeling of mineralized bodies can be used in surface and / or underground waters in their lagoon and aquifer aspects, respectively. This work proposes the application of the use of drilling rigs, but this time carried out for bodies of water on the surface and / or underground, with the same techniques of witnessing and logging; but with the difference of the techniques used, the same ones detailed below.